The effects of valproic acid on navi.5 gene expression in mda-mb- 231 cells - Kandivan, Hemalatha (Universiti Sains Malaysia, 2016)
Over the past few decades, breast cancer researches have been ongoing and new treatments are being discovered every year to improve patients’ quality of life. However, metastasis remains largely as the cause of cancer mortality and metastatic-targeted therapies are being studied, hi the highly metastatic human breast cancer cell line, MDAMB- 231, cardiac voltage-gated sodium channel Navi.5 and its neonatal splice variant, nNavl.5 were found to be overexpressed and strongly linked to metastatic behavior of the cells. Previous studies have proved valproic acid’s anti-tumor effects in different types of cancer cells. In this study, valproic acid, an anticonvulsant known to inhibit voltage-gated sodium channels, was used to study its effects on MDA-MB-231 cell motility and viability as well as the gene expression of Navi.5 and nNavl.5 in MDA-MB-231 cells. Functional assays such as MTT and lateral motility assays were conducted to study the viability and motility of the cells. For molecular assay, real-time polymerase chain reaction was employed to study Navi.5 and neonatal Navi.5 gene expression. MTT assay showed a decline in MDA-MB-231 cell viability with increasing concentrations of valproic acid. The same trend was observed in lateral motility assay, which showed reduction in motility of MDA-MB-231 cells. The suppression of metastatic behavior (lateral motility) was followed by down-regulation of Navi.5 and neonatal Navi.5 gene expression with the highest concentration of valproic acid. From the findings, it can be deduced that valproic acid has great potential to be included in aggressive breast cancer therapy and further research should be done to investigate its other anti-metastatic properties in breast cancer.